Acetylation in Tumor Immune Evasion Regulation - Lu, Jun; He, Xiang; Zhang, Lijuan; Zhang, Ran; Li, Wenzheng (Frontiers in Pharmacology, 2021)
Acetylation is considered as one of the most common types of epigenetic modifications, and aberrant histone acetylation modifications are associated with the pathological process of cancer through the regulation of oncogenes and tumor suppressors. Recent studies have shown that immune system function and tumor immunity can also be affected by acetylation modifications. A comprehensive understanding of the role of acetylation function in cancer is essential, which may help to develop new therapies to improve the prognosis of cancer patients. In this review, we mainly discussed the functions of acetylase and deacetylase in tumor, immune system and tumor immunity, and listed the information of drugs targeting these enzymes in tumor immunotherapy.